PEMAHAMAN KELOMPOK WANITA TANI âMELATI PUTIH IIâ KELURAHAN BANDUNGREJOSARI KECAMATAN SUKUN KOTA - Asmawati, Anastasia; Masduki, Said; Suwasono, Son (Fakultas Pertanian, 2019)
Area Homes Preserved Food (AHPF) is a program of the Ministry of agriculture against the attitude of positive or negative environment. Lawns generally untapped optimally, both in an effort to meet the needs of the household and as a means to supplement the family income, so most of the functions of the grounds for this just serves as means of aesthetics only. This research aims to describe KRPL relating to understanding. This research was carried out in June-August 2017 in Kelurahan of Bandungrejosari sub-district of Breadfruit Malang. The method of research used Descriptive Qualitative with the help of Excel for windows to get in-depth data is done with the interview, questionnaire and observation (observation) with a total sample of 34 people. Based on the results of the study showed that the understanding of the members of the Group of women farmers KRPL retrieved results ; find out the program: History of KRPL, head of the PKK, and extension officers/PPL as much as 52.94%, from: Chairman of the Rt, Rw and neighbors as much as 47.05%; never accept a material extension officers; ways of making verticultur or terraced crops as much as 50%, manufacture of liquid manure by as much as 50%; following training in the village and in the village Hall as much as 67.64% Rt Rw and, in as much as 32.35%; nursery nurseries; using pot and poly bag as much as 55.88%, racks, and bottles as much as 44.11%; never accept help; seeds, and seed as much as 70.58%, pots, polybag and paralon as much as 29.41%; land area yards > 50 m2 for as much as 40% and < 20.58 m2 as much as 79.41%. Kawasan Rumah Pangan Lestari (KRPL) merupakan salah satu program Kementerian Pertanian terhadap sikap peduli lingkungan positif maupun negatif. Pekarangan pada umumnya belum dimanfaatkan secara optimal, baik dalam usaha untuk memenuhi kebutuhan rumah tangga maupun sebagai sarana untuk menambah penghasilan keluarga, sehingga sebagian besar fungsi dari pekarangan selama ini hanya berfungsi sebagai sarana estetika saja. Penelitian ini bertujuan untuk mendeskripsikan KRPL dan dilaksanakan pada bulan Juni-Agustus 2017 di Kelurahan Bandungrejosari Kecamatan Sukun Kota Malang. Metode penelitian yang digunakan Deskriptif Kualitatif dengan bantuan Excel for windows untuk mendapatkan data dilakukan dengan wawancara, kuesioner dan pengamatan (observasi) dengan jumlah sampel 34 orang. Berdasarkan hasil penelitian menunjukan bahwa Pemahaman anggota kelompok wanita tani KRPL diperoleh yaitu; mengetahui program KRPL dari: Lurah, Ketua PKK, dan Penyuluh/PPL sebanyak 52,94%, dari: Ketua Rt, Rw dan Tetangga sebanyak 47,05%; pernah menerima materi penyuluh; cara pembuatan vertikultur sebanyak 50%, pembuatan pupuk cair sebanyak 50%; mengikuti pelatihan di Kelurahan dan di Balai Desa sebanyak 67,64%, di Rw dan Rt sebanyak 32,35%; persemaian kebun bibit; menggunakan pot dan polybag sebanyak 55,88%, rak, dan botol bekas sebanyak 44,11%; pernah menerima bantuan; bibit, dan benih sebanyak 70,58%, pot, polybag dan paralon sebanyak 29,41%; luas lahan pekarangan >50 m2 sebanyak 20,58% dan